PEMBERDAYAAN ORANG TUA DALAM STIMULASI BAYI DENGAN PELATIHAN BABY MASSAGE - Ratna Wulan Purnami; Fanny Aulia Azizah (LPPM STIKES Madani Yogyakarta, 2019)
Massage is the oldest known and most popular touch therapy. Massage is an art of health care and medicine that has been practiced for centuries. Stimulation is an important thing in children development. Parents provide stimulation to baby in order to provide good benefits for the development of children. A good growth and development stimulation can be given by parents to their babies by baby massage. The skills about baby massage are still not widely known by the public. Even some parents' awareness is still less related to stimulation of baby's growth. One of the problems in Dusun Karang Tengah is the low percentage of participation in monitoring the detection of child growth, which one of the indicators can be seen in the participation of children weighing activity (57.1%). Therefore it is necessary to encourage baby's parents in stimulating the growth and development of babies with baby massage training, so that the bounding between babies and parents can also be closer and the time of togetherness with the baby can be more qualified. The classical approach was conducted when giving the theory of baby massage and individual approaches are carried out during the practice of baby massage demonstrations to the baby or phantom. This activity increased understanding and skills of mothers who have babies about baby massage.